Megninia ginglymura feather mite infestation in a Hamburg poultry flock in the United Kingdom. Issue 2 (24th February 2016) - Van Poucke, Stefaan; Creighton, Robin; Baker, Anne S.
Abstract : Background: A flock of rare breed poultry was heavily infested with small white mites. Although apparently not harming the birds, the mites were identified in order to access data on veterinary/medical significance and to decide upon appropriate treatment. Objectives: To determine the identity of the mites, assess their potential impact on the host birds and to apply a chemical treatment regime. Animals: Twelve, 5‐month‐old Hamburg large fowl kept on a UK farm owned by the second author. They were housed together on shavings in an indoor pen with a grass outdoor run. All were hatched on the farm and never left it. Methods: Mites were identified using taxonomic identification keys and morphological descriptions. Nine birds were treated topically with 0.25% fipronil at 8 mL/kg on one occasion, while three birds were separated and left untreated as a control. Results: The infesting species was the feather mite Megninia ginglymura . Treated birds were mite‐free after three weeks, whereas untreated ones were still heavily infested. Conclusions and clinical importance: This is the first published report of such a heavy infestation of M. ginglymura in poultry in the UK and the first time topical fipronil has been used to eradicate these mites. The case is highlighted because, although asymptomatic in this instance, such infestations may be injurious to birds in different rearing regimes. Abstract : Background – A flock of rare breed poultry was heavily infested with small white mites. Although apparently not harming the birds, the mites were identified in order to access data on veterinary/medical significance and to decide upon appropriate treatment.Objectives – To determine the identity of the mites, assess their potential impact on the host birds and to apply a chemical treatment regime.Conclusions and clinical importance – This is the first published report of such a heavy infestation of Megninia ginglymura in poultry in the UK and the first time topical fipronil was used to eradicate these mites. The case is highlighted because, although asymptomatic in this instance, such infestations may be injurious to birds in different rearing regimes.